Secular dealignment and party system transition in Malaysia - Moten, Abdul Rashid (Cambridge University Press, 2013)
The Malaysian electoral behaviour has for some time reflected the ‘partisan identification’ thesis. Since 1999, however, there has been a marked shift towards ‘secular dealignment’. Analyses of electoral and survey data reveal that although a significant number of Malaysian voters remained attached to the party they identified with, most of the electorate, however, are swayed by short-term factors. Though the economic issues played a role in the three elections, it is the leadership of the parties supplemented by the use of mass media that played a significant role in swinging the vote from one party to the other. The three elections in 1999, 2004, and 2008 can be categorized as evidence of secular dealignment: the 1999 elections substantially reduced the margin of gain by the ruling coalition; the 2004 elections reversed the opposition gain, while the 2008 elections resulted in the loss of two-thirds majority seats in the parliament habitually enjoyed by the ruling coalition and the emergence of a strong opposition coalition. This trend not merely continued but was much more stronger in the 13th Malaysian general election.